An estimation of inflation threshold for Africa - Ikechukwu Kelikume (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
The objective of this study was to shed new light on the non-linear effects of inflation and the inflation thresholds for long-term growth in Africa. Using a dynamic panel threshold model, the study covered a large panel-data set of 41 African countries for the period 1960-2015. The sample was divided into 21 resource rich countries and 20 non-resource rich countries in order to see if there are any differences in the empirical linkage between inflation and long-term growth. For the full sample of African countries, the empirical evidence showed that inflation hampered growth if it exceeds 11.1 percent. Below this threshold, however, the impact of inflation on growth remained positive though insignificant. However, the results differed for resource rich and non-resource rich African countries: inflation was beneficial for growth when inflation is below 12.5 percent and 9.4 percent threshold levels for resource rich and non-resource rich African countries, respectively. However, when inflation exceeded these threshold levels, it had a negative effect on growth. The estimated inflation threshold value for resource rich countries was definitely more than in non-resource rich countries. The evidence clearly suggested a growth-dampening effect of excessive inflation for Africa.
Keywords: C01; C23; C33; E31; O40; O57; 330; Inflation threshold; inflation; long-term growth; dynamic panel threshold model; non-linear relationship